Chemotherapy remains an essential element of personalized care for persons with lung cancers - Hellmann, M. D. (Ann Oncol, 2016)
Molecularly targeted and immunotherapies have improved the care of patients with lung cancers. These successes have rallied calls to replace or avoid chemotherapy. Yet, even in this era of precision medicine and exciting advances, cytotoxic chemotherapies remain an essential component of lung cancer treatment. In the setting of locoregional disease, chemotherapy is the only systemic therapy thus far proven to enhance curability when combined with surgery or radiation. In the metastatic setting, chemotherapy can improve the length and quality of life in many patients. Chemotherapy remains the mainstay of care for individuals whose cancers with oncogenic drivers have acquired resistance to targeted agents. Chemotherapy also has the potential to modulate the immune system to enhance the effectiveness of immune checkpoint inhibitors. In this context, chemotherapy should be framed as a critical component of the armamentarium available for optimizing cancer care rather than an unfortunate anachronism. We examine the role of chemotherapy with precision medicine in the current care of patients with lung cancers, as well as opportunities for future integration in combinations with targeted agents, angiogenesis inhibitors, immunotherapies, and antibody drug conjugates.